The inheritance games - Barnes, Jennifer (Jennifer Lynn) (Little, Brown and Company, 2020)
Avery Grambs has plans for her future: survive high school, win a scholarship, and get far away. But when billionaire Tobias Hawthorne dies and leaves Avery nearly his entire fortune, her life changes in an instant. The problem? Avery has no idea who Tobias Hawthorne was or why he would leave her his fortune. To receive her inheritance, Avery must move into Hawthorne House, which is filled with secret passages, puzzles, codes, and the family that Avery just dispossessed. Avery will have to go up against Tobias's scheming daughters and four grandsons, who are convinced that she's either a con-woman or another puzzle to be solved.